Answer:
The cost of total lunch is 1.18 y ( 1+ 0.0 x )
Step-by-step explanation:
Given as :
The percentage of tip added tot he bill after tax = 18 %
Let the tax added to the bill = x % of total the lunch price
Let The total lunch cost = y
So, The cost of the lunch after tax = y + x % × y
I.e The cost of lunch after tax = y × ( 1 +x % )
Or. The bill of lunch after tax = y × ( 1 + 0.0 x )
Now the cost of lunch after tax and tip =18 % of y × ( 1 + 0.0 x ) + y × ( 1 + 0.0 x )
Or, the cost of lunch after tax and tip = y × ( 1 + 0.0 x ) (0.18 + 1 )
∴ The cost of lunch after tax and tip = y × ( 1 + 0.0 x ) × 1.18
Hence The cost of total lunch is 1.18 y ( 1+ 0.0 x ) Answer
6. Emma uses 10 pages of paper when she writes anything. She uses an
additional 4 pages of paper every hour that she writes. Write an equation
that would show how many pages of paper she uses when writing.
Answer:
4x+10
Step-by-step explanation:
Emma is guaranteed to use 10 pages when she writes something. Since you can't tell how many hours she has written, you use x to represent the hours she has spent writing. If she writes 4 pages every hour, that would be 4 × (hours spent writing) or 4x. Add 4x to the original guaranteed 10 pages she uses and you have your expression.
Leroux Health Insurance is considering changing the options in one of their health care plans (Plan A) based on customer feedback that prescriptions and regular visits to the doctor are too expensive for the insured individual. How can Leroux reduce the costs of regular health care without driving up the price of their health care plan?
a.
Reduce the monthly premium but increase the co-pay amounts to compensate for the lower premium.
b.
Reduce the annual deductible, but increase the co-pay amounts so that the monthly premium can stay the same.
c.
Reduce the co-pay amounts but increase the annual deductible so that the monthly premium can stay the same.
d.
Reduce the co-pay amounts but increase the monthly premium to compensate for the lower deductible.
The best way that Leroux can reduce the costs of regular health care without driving up the price of their health care plan is this: c. Reduce the co-pay amounts but increase the annual deductible so that the monthly premium can stay the same.
What is the best way to reduce costs?The best way that Leroux can reduce the costs of regular health care without increasing the price of the plan would be for then to reduce the co-pay amounts and then increase the annual deductible.
Annual deductibles are the amounts that the customers are expected to pay themselves while the premium is covered by the health company.
Learn more about annual deductibles here:
https://brainly.com/question/31268143
#SPJ3
Which equation shows y=-x+4 is in standard form?
2x - y=8
Ox+2y=-8
O
x + 2y = 8
2x + y = 8
Answer:
(c) [tex]x + 2y = 8[/tex]
Step-by-step explanation:
The question is missing some important data which is necessary to solve it.
The correct question is as follows:
Which equation shows [tex]y=-\frac{1}{2}x+4[/tex] is in standard form?
(a) [tex]2x-y=8[/tex]
(b) [tex]x + 2y=-8[/tex]
(c) [tex]x + 2y = 8[/tex]
(d) [tex]2x + y = 8[/tex]
Solution:
Given equation:
[tex]y=-\frac{1}{2}x+4[/tex]
To convert the given equation to standard form.
The standard form of a linear equation is given by:
[tex]Ax+By=c[/tex]
where
A is a positive integer and B and C are integers
We have:
[tex]y=-\frac{1}{2}x+4[/tex]
Multiply both sides by 2 to remove the fraction
[tex]2y=(-\frac{1}{2}x\times 2)+(4\times 2)[/tex]
[tex]2y=-x+8[/tex]
Adding [tex]x[/tex] both sides
[tex]x+2y=x-x+8[/tex]
[tex]x+2y=8[/tex]
∴ The standard form of the equation is ⇒ [tex]x+2y=8[/tex]
Jerry has 9 keys on his keyring. 4 of them are silver and 5 are gold. If he randomly chooses a key.
what is the probability that the key would be silver?
Answer:
Silver keys = 4
Gold keys = 5
Total number of keys = 9
probability of getting a silver key = P(4/9)
Step-by-step explanation:
P(4/9) because 4 keys are silver among 9 keys. Probability is the number of chosen matter divided by the total number of matters.
What is the image of −6,3)
(−6,3) after a reflection over the y-axis?
Final answer:
The image of the point (-6,3) after a reflection over the y-axis is (6,3), because a reflection over the y-axis changes the sign of the x-coordinate while leaving the y-coordinate unchanged.
Explanation:
The question is asking for the result of a reflection of the point (-6,3) over the y-axis. A reflection over the y-axis will invert the x-coordinate of the point but leave the y-coordinate unchanged. Hence, the reflected point will have the same y-coordinate but the opposite x-coordinate. The transformation formula for a reflection over the y-axis is (x, y) to (-x, y).
Applying this formula to the point (-6,3), we change the sign of the x-coordinate from -6 to 6, while the y-coordinate remains the same. Therefore, the image of the point (-6,3) after the reflection over the y-axis is (6,3).
The function y=ex is vertically stretched by a factor of 2, reflected across the x-axis, and then shifted down 3 units, find the resulting function.
Provide your answer below:
Answer:
1/2e^x -3
Step-by-step explanation:
The resulting function after vertically stretching y = ex by a factor of 2, reflecting it across the x-axis, and shifting it down 3 units is y = -2ex - 3.
Explanation:The original function is y = ex. To find the resulting function after the described transformations (vertically stretched by a factor of 2, reflected across the x-axis, and shifted down 3 units), we perform each transformation step by step.
Vertical Stretch: Multiplying the function by 2 gives us 2ex.Reflection across the x-axis: Multiplying by -1 to reflect it gives us -2ex.Shift down by 3 units: Subtracting 3 from the function gives us -2ex - 3.Therefore, the resulting function after all transformations is y = -2ex - 3.
how can you find the function rule from a table of values
20 points for this question:
Find the domain.
Answer:
The Domain D = {y ∈ R / y ≠ [tex]\dfrac{b}{2}[/tex] y ≠ 0}
Step-by-step explanation:
Let ,
f(y) = [tex]\dfrac{b^{2} - 4by }{2y^{2} - by }[/tex] - [tex]\dfrac{4y}{b-2y}[/tex]
The above function would be defined only when the denominator of anyone or both the terms of the function do not become 0 -
[tex]2y^{2} - by[/tex] ≠ 0 and b - 2y ≠ 0
∴ y(2y - b) ≠ 0 and y ≠[tex]\dfrac{b}{2}[/tex]
Either y ≠ 0 or y ≠ [tex]\dfrac{b}{2}[/tex]
∵ The domain of a function consists of only those points where the function is defined -
The Domain D consists of all y ∈ Real numbers such that y ≠ 0 and y ≠ [tex]\dfrac{b}{2}[/tex]
Peter filled 5 cups each with 1 pound of candy. How much candy did the 5 cups contain altogether? 5 1/2 pounds
6 1/2 pounds 7 pounds 7 1/2 pounds
Step-by-step explanation: i think it is B
Jack and Julio each improved their yards by planting daylilies and geraniums. They bought their supplies from the same store.
Jack spent $22 on 1 daylily and 5 geraniums. Julio spent $30 on 13 daylilies and 1 geranium. Find the cost of one daylily.
Cost of one daylily is $2 and cost of one geranium is $4.
Step-by-step explanation:
Let,
Cost of one daylily = x
Cost of one geranium = y
According to given statement;
x+5y=22 Eqn 1
13x+y=30 Eqn 2
From Eqn 1;
x=22 - 5y
Putting this value of x in Eqn 2;
[tex]13(22-5y)+y=30\\286-65y+y=30\\-64y=30-286\\-64y=-256[/tex]
Dividing both sides by -64
[tex]\frac{-64y}{-64}=\frac{-256}{-64}\\y=4[/tex]
Putting y=4 in Eqn 1
[tex]x+5(4)=22\\x+20=22\\x=22-20\\x=2[/tex]
Cost of one daylily is $2 and cost of one geranium is $4.
Keywords: linear equation, substitution method
Learn more about substitution method at:
brainly.com/question/605571brainly.com/question/5873564#LearnwithBrainly
What is the standard to slope intercept form 4x - 4y = -8
Answer:
y = x + 2
Step-by-step explanation:
4x - 4y = -8 can be rearranged to slope-intercept form by isolating y.
[tex]4x - 4y = -8\\-4y = -8 - 4x\\y =\frac{-8-4x}{-4} \\y = 2 + x\\y = x + 2[/tex]
How can ΔABC be mapped to ΔXYZ?
Triangles A B C and X Y Z are shown. The lengths of sides A B and X Y are 25 centimeters. The lengths of sides A C and X Z are 29 centimeters. Angles B A C and Y X Z are 36 degrees. Triangle A B C is slightly higher and to the left of triangle X Y Z. Triangle A B C is rotated to form triangle X Y Z.
First, translate ____________________. Next, rotate ΔABC about B to align the sides and angles.
vertex B to vertex Z
vertex B to vertex Y
vertex A to vertex Z
vertex A to vertex Y
Answer:
Vertex B to vertex Y
Step-by-step explanation:
The diagram shows two triangles ABC and XYZ. These triangles are congruent by SAS postulate, because
AB = XY = 25 cm;AC = XZ = 29 cm;∠A = ∠X = 36°.Congruent triangles have congruent corresponding sides and angles, so translation and rotation must be completed such that
vertex A coincides with vertex X;vertex B coincides with vertex Y;vertex C coincides with vertex Z.So, first, translate vertex B to vertex Y. Next, rotate ΔABC about B to align the sides and angles.
I can't figure out what I'm doing wrong can you please help me I'll give you a lot of points and this this really hard :(
MICKEY AND MINNIE ARE EXPECTING.
THEY ARE A VERY HAPPY COUPLE.
THE DOCTOR SAID THEY ARE HAVING 5 BOYS AND 5 GIRLS.
MICKEY AND MINNIE ARE RATS.
EVERY THREE WEEKS AN ADULT RAT COUPLE CAN HAVE BABIES.
IT TAKES 6 WEEKS FOR A BABY RAT TO BECOME AN ADULT
AND BE OLD ENOUGH TO HAVE A BABY.
ASSUMING MICKEY AND MINNIE WANT TO HAVE AS MANY CHILDREN AS POSSIBLE AND THEIR OFFSPRING WANT TO HAVE AS MANY CHILDREN AS POSSIBLE,
WHAT WILL BE THEIR ENTIRE POPULATION IN ONE YEAR? (52 WEEKS)
(INCLUDING MICKEY AND MINNIE)
(ASSUME EVERY PREGNACY WILL CONSIST OF 5 BOYS AND 5 GIRLS)
Answer:
1,495,672
Step-by-step explanation:
Build a table to track the number of adult rats, 3-week old rats (let's call them teens), and baby rats.
[tex]\left[\begin{array}{ccccc}Week&Adult&Teen&Baby\\1&2&0&0\\3&2&0&10\\6&2&10&10\\9&12&10&10\\12&22&10&60\\15&32&60&110\\18&92&110&160\end{array}\right][/tex]
The pattern is this: every 3 weeks, the number of adults becomes the previous number of adults + the number of teens. The number of teens becomes the previous number of babies. And the number of babies becomes the previous number of adults × 5.
Continuing:
[tex]\left[\begin{array}{ccccc}Week&Adult&Teen&Baby\\1&2&0&0\\3&2&0&10\\6&2&10&10\\9&12&10&10\\12&22&10&60\\15&32&60&110\\18&92&110&160\\21&202&160&460\\24&362&460&1010\\27&822&1010&1810\\30&1832&1810&4110\\33&3642&4110&9160\\36&7752&9160&18210\\39&16912&18210&38760\\42&35122&38760&84560\\45&73882&84560&175610\\48&158442&175610&369410\\51&334052&369410&792210\end{array}\right][/tex]
So at the end of the year, there are a total of 1,495,672 rats.
Which expression is equivalent to
3(x + 6)?
F. x + 3 + 6
G. 3x + 6
H. x+6
J. 3x + 18
Answer:3x+18
Step-by-step explanation:
Which equation is equivalent to 3=87/h?
Answer:
h=87/3
Step-by-step explanation:
3=87/h
h=87/3
how much horsepower would a Challenger SRT® Hellcat Redeye Widebody need to tow the SS Delphine up the industry standard: Davis Dam Grade Climb?
Pro Tips:
Davis Dam assumed grade = 7% Air density is sea level conditions (.002377 slugs/f^t3) w(weight) of the SS Delphine + trailer + Redeye = 3,922,000 + 150,000 + 4451 Lbs Crr = coefficient of rolling resistance = .015 Assume Combined CDA is 1555 ft^2 SAE J2807 (Davis Dam Grande Climb) - min speed is 40mpg (59 ft/s) F(drag) = 1/2p x V^2 x C(d)A F(rolling resistance) = W x cos x Crr F(weight) = W x sin F(sum) = F(drag) + F(rr) + F(weight) P = F(sum)XV convert to horsepower = P(1hp/550ft lbf/sec)
Answer: I am getting a result around the 54,800 area, so I am selecting the 55,000 HP answer.
Answer:
37769 hp
Step-by-step explanation:
from the pro tips given w ( weight of the SS Delphine + trailer + Redeye) = 3922000 + 150000 + 4451 Lbs Crr = 4076451 ibf
coefficient of rolling resistance = 0.015
Combined CDA = 1555 ft ^2
to get Ф = tan ⁻¹ ( 0.07 ) = 4.0041 degrees
To get F (w) you will multiply it with sin Ф
= F ( w ) = 4076451 ibf * sin( 4.0041 ) = 284655.02 Ibf
to calculate F ( rr ) you will multiply it with cos Ф
F( rr) = 4076451 ibf * 0.015 * cos ( 4.0041 ) = 60997.50 ibf
the total sum of F ( force ) will be
F ( rr ) + F ( w)
= 60997.50 + 284655.02 = 352085.82 Ibf
therefore P ( power ) will be
p = 352085.82 ibf * 59 ft/s = 20773063.27 ft*ibf/s
to calculate how much horsepower the challenger will need to tow the SS Delphine will be calculated as below
HP = (20773063.27 ft*ibf/s ) * ( 1 hp / 550 ft*ibf/s ) = 37769.21 = 37769 hp
Write the word sentence as an inequality.
The quotient of a number g and -2 is fewer than -6.
An inequality is a
Answer:
[tex]\displaystyle -6 > \frac{g}{-2}[/tex]
Step-by-step explanation:
[tex]\displaystyle \frac{g}{-2} < -6[/tex]
The keywords are fewer than, so the inequality receives the less than symbol, NOT greater than or equal to.
** The above answer is written in reverse, which is the exact same result.
I am joyous to assist you anytime.
The word sentence translates to the inequality 'g / -2 < -6', representing the relationship where the quotient of a number g and -2 is less than -6.
Writing the word sentence 'The quotient of a number g and -2 is fewer than -6' as an inequality involves translating the words into a mathematical expression. Inequality symbols are used to show how two measurements, or in this case, expressions, are related. The quotient of a number and another number is represented by the division of those two numbers. 'Fewer than' indicates that the expression on the left side is less than (<) the expression or value on the right side.
Therefore, the statement can be translated to the mathematical inequality as g / -2 < -6. This inequality shows the relationship between the variable g and the numbers -2 and -6, with the quotient of g and -2 being less than -6.
Select the correct answer.
The formula for finding the kinetic energy, E, of an object is given below, where m represents the mass and v represents the speed of
the object.
E = mv2
Solve the formula for v.
You can solve the kinetic energy formula E = mv² for 'v' by first dividing by 'm' to get E/m = v² and then taking the square root of both sides, resulting in v = sqrt(E/m).
Explanation:The kinetic energy of an object is given by the equation E = mv², where 'm' is the mass of the object and 'v' is its speed. If you want to solve this formula for 'v', you would start by dividing both sides of the equation by 'm'. Doing this, you would get: E/m = v². Then, you would take the square root of both sides to isolate 'v'. This would give you: v = sqrt(E/m), where sqrt stands for 'square root'.
This means that the speed of the object can be found by taking the square root of the kinetic energy divided by the mass of the object.
Learn more about Kinetic Energy here:https://brainly.com/question/26472013
#SPJ12
The expression for y is y = [tex]\frac{2E}{m}[/tex].
To solve the kinetic energy formula E=[tex]\frac{1}{2}[/tex] [tex]mv^{2}[/tex] for y, we need to isolate y on one side of the equation. The formula can be rearranged as follows:
E=[tex]\frac{1}{2}[/tex][tex]mv^{2}[/tex]
Multiply both sides of the equation by 2 to eliminate the fraction:
2 E = [tex]mv^{2}[/tex]
Now, to solve for y, which is represented by [tex]mv^{2}[/tex] , divide both sides by m:
y = [tex]\frac{2E}{m}[/tex]
So, the expression for y is y = [tex]\frac{2E}{m}[/tex] .
This final equation tells us that y (representing [tex]mv^{2}[/tex] ) is equal to twice the kinetic energy (E) divided by the mass (m) of the object.
In physics, [tex]mv^{2}[/tex] is often associated with momentum or the force needed to change the object's velocity.
This derived formula provides a clear representation of the relationship between kinetic energy, mass, and velocity in terms of y.
Question
The formula for finding the kinetic energy, E, of an object is given below, where m represents the mass and v represents the speed of the object. E= 1/2 mv^2 Solve the formula for y.
Tom simplified an expression in three steps, as shown:
Which is the first incorrect step and why?
Step 1, all the exponents are increased by 4
Step 2, the exponents of the same base are added during multiplication
Step 3, the exponents of the same base are subtracted during division
Step 3, all the exponents are added during division
Answer:
Step 1) is incorrect.
Step-by-step explanation:
Answer:
Step one is the one that is wrong
Step-by-step explanation:
Cat hacker
how long will it take for an investment to triple if it is compounded continuously at 12%
Answer:
9.694 years
Step-by-step explanation:
Let the investment is $P.
So, we are asked to determine the time it will grow to triple with the compound interest rate of 12%.
Let the time is y years.
So, from the formula of compound interest we can write
[tex]3P = P(1 + \frac{12}{100} )^{y}[/tex]
⇒ [tex](1 + \frac{12}{100} )^{y} = 3[/tex]
⇒ [tex](1.12)^{y} = 3[/tex]
Now, taking log both sides we get,
y log 1.12 = log 3 {Since, [tex]\log a^{b} = b \log a[/tex] }
⇒ 0.04922y = 0.477712
⇒ y = 9.694 years (Answer)
y-1=-2(x+3) in standard form
Answer:
2x + y + 5 = 0
Step-by-step explanation:
y − 1 = -2 (x + 3)
y − 1 = -2x − 6
2x + y + 5 = 0
Match the real-world problem to its constant of proportionality.
a. $18.36 for 3 pizzas [box]
b. $4.17 for 3 pounds of bananas [box]
c. $16.48 for 4 pounds of potatoes [box]
d. 2 cups of flour to make 24 cookies [box]
Place in the box 12 4.12 6.12 1.39
WIN BRAINLIEST
Answer:
a. $18.36 for 3 pizzas : k = 6.12
b. $4.17 for 3 pounds of bananas . k = 1.39
c. $16.48 for 4 pounds of potatoes . k = 4.12
d. 2 cups of flour to make 24 cookie . k = 12
Step-by-step explanation:
PROPORTIONALITY:
Two quantities x and y are said to proportional to each other
if for x ∝ y , x = y k.
Here, k is called the PROPORTIONALITY CONSTANT.
⇒[tex]x \propto y \implies k = \frac{x}{y}[/tex]
Now, for the given quantities:
a. $18.36 for 3 pizzas [box]
Here, [tex]k = \frac{x}{y} = \frac{18.36}{3} = 6.12[/tex]
So, the proportionality constant is 6.12.
b. $4.17 for 3 pounds of bananas [box]
Here, [tex]k = \frac{x}{y} = \frac{4.17}{3} = 1.39[/tex]
So, the proportionality constant is 1.39.
c. $16.48 for 4 pounds of potatoes [box]
Here, [tex]k = \frac{x}{y} = \frac{16.48}{4} = 4.12[/tex]
So, the proportionality constant is 4.12.
d. 2 cups of flour to make 24 cookies
Here, [tex]k = \frac{x}{y} = \frac{24}{2} = 12[/tex]
So, the proportionality constant is 12.
the price of a gallon of heating oil rose from 1.60 a gallon to 1.92 . by what percent did the price increase?
Answer:
20%
Step-by-step explanation:
1.92 - 1.60 = 0.32
percentage increase = (0.32/1.60) * 100 =
0.2 * 100 = 20%
Answer: required percent increase in price=20%
Step-by-step explanation:
required percent increase in price=[tex]\frac{1.92-1.60}{1.60}[/tex]\times100
=[tex]\frac{0.32}{1.60}[/tex]\times100
=[tex]0.20\times100[/tex]
=20%
answer the question below please answer correctly
Answer:
x=4
Step-by-step explanation:
Using cross multiplication, we can simplify the equation to
-15x=-60
Then we can divide by -15 on both sides getting x=4
A Job hotline service charges $25 plus a 4% commission c on the first month of earning if it finds work for a client. Write an equation that represents the total cost T to find a job through the hotline. What is the cost of a client earns $1500 the first month
Answer: Equation for total cost: T = $25 + 0.04E
Cost of a client who earns $1500 = $85
Step-by-step explanation:
Let E = earning in the first month
Commission (c) = 0.04 (4%) × E
Total cost will be the addition of $25 fixed amount and commission
Therefore, an equation that will represent total cost of finding a job through the hotline will be:
T = $25 + 0.04E
The cost of a client whose first month earnings is $1500 will be
T = $25 + 0.04 ($1500)
T = $25 + $60 = $85
I found that helpful
wuts 4x +6x= plzzzzzzzzzzzzzz help me im in 4th grade
Answer:
10x
Step-by-step explanation:
Answer:
10x
Step-by-step explanation:
since they both are the same just add them and done
I have a precalculus problem about solving the equation can somebody help me please
Answer:
Yeah
Step-by-step explanation:
find a formula
7 more than the product of 8 and 4
Answer:
39
Step-by-step explanation:
product = 2 numbers multiplied by each other
8 x 4 = 32
32 + 7 = 39
The product of two numbers is when you multiply those two numbers together.
So, the product of 8 and 4 would simply be 8 * 4=32
7 more than 32 would simply be 32 + 7=39
The answer is 39
Jo is thinking of a number. Four less than 9 times the number is 176. Find Jo’s number.
Answer:
Jo's thinking about the number 20.
Step-by-step explanation:
9x-4=176
9x=176+4
9x=180
x=180/9
x=20
What triangle congruence postulate would prove that the two triangles are congruent?
Answer:
SAS
Step-by-step explanation: